Kewenangan Notaris Yang Merangkap Jabatan Menjadi Pejabat Lelang Kelas II - Yasa, I Gusti Ayu Githa Dewantari; Priyanto, I Made Dedy (Acta Comitas : Jurnal Hukum Kenotariatan, 2024)
This article aims to examine whether all notaries can make auction minutes deeds and what the authority of a notary who doubles as an auction official is. The notary is given the authority to make an auction minutes deed which can be linked to the Auction regulation which gives this authority. This research uses a normative juridical research method where there is a blurring of norms in the provisions on notaries having authority to make auction minutes deeds. The results of this research are that notaries and auction officials are both public officials who can make authentic deeds, but not all notaries can make auction minutes deeds. The auction minutes deed can only be made by a notary who has completed several provisions to become an auction official.